Aplikasi Belajar Matematika Sekolah Dasar Kelas V Berbasis Mobile Android - Suliswaningsih Suliswaningsih; Aris Purnomo; Septi Fajarwati; Agung Prasetyo; Dani Arifudin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
SD Negeri 3 Tugu uses the 2013 curriculum, which is an integrative thematic learning method, a scientific approach, and an authentic assessment. The method used is lecture, discussion, experiment, question and answer, skills, problem-solving, and assignments. Teachers at SD Negeri 3 Tugu use blackboards, notebooks, and textbooks as the media. Based on the results of interviews with fifth-grade students and teachers, it was stated that some students had difficulty understanding the mathematics material presented by the teacher in class. The number of formulas that must be understood by students, difficulties when doing assignments/Homework (PR) given by the teacher. This resulted in students getting poor grades in mathematics courses. The purpose of the research is to create an Android-based learning media application for grade V elementary school mathematics as an independent learning medium and help increase student interest in learning. The research uses the extreme programming method which includes the design stage to model the system from the application of mathematics learning media, the coding stage, namely the implementation of the system design using Microsoft Visual Studio software, and the testing stage using a questionnaire and involving material experts with an average of 84.28%, media experts as much as 91.42%, and student respondents as much as 84.28%. The results of the study indicate that the average respondent strongly agrees that the application is suitable for use as an Android mobile-based mathematics learning media.